Efficient neocentromere formation is suppressed by gene conversion to maintain centromere function at native physical chromosomal loci in Candida albicans - Thakur, Jitendra; Sanyal, Kaustuv

(untitled) (Genome Research, 2013)
CENPA/Cse4 assembles centromeric chromatin on diverse DNA. CENPA chromatin is epigenetically propagated on unique and different centromere DNA sequences in a pathogenic yeast Candida albicans. Formation of neocentromeres on DNA, nonhomologous to native centromeres, indicates a role of non-DNA sequence determinants in CENPA deposition. Neocentromeres have been shown to form at multiple loci in C. albicans when a native centromere was deleted. However, the process of site selection for CENPA deposition on native or neocentromeres in the absence of defined DNA sequences remains elusive. By systematic deletion of CENPA chromatin-containing regions of variable length of different chromosomes, followed by mapping of neocentromere loci in C. albicans and its related species Candida dubliniensis, which share similar centromere properties, we demonstrate that the chromosomal location is an evolutionarily conserved primary determinant of CENPA deposition. Neocentromeres on the altered chromosome are always formed close to the site which was once occupied by the native centromere. Interestingly, repositioning of CENPA chromatin from the neocentromere to the native centromere occurs by gene conversion in C. albicans.